International Trade During the Crisis. Determinants - Cristian Spiridon (CES Working Papers, 2014)
This article aims to analyze how the financial crisis that bursted in the mid-2008 led to a global and regional drop in trade flows. It starts from a comparison of the Great Depression shock to what happened during the Great Recession. Based on the similarities and differences found in the literature we take a simple econometric analysis to study the relationship between income, private lending and imports of goods by different countries from the financial meltdown starting point. The main findings consist of the magnitude heterogeneity of the decrease in income and credit at the regional level and on country groups according to the degree of development and the uttering of new factors influencing world trade (risk shock, increasing uncertainty, escalating non-tariff protectionist measures).
Keywords: F01; F13; F14; F17; F23; 330; international trade; financial crisis; Great Depression; Great Recession Romania